PIM research used to develop school gardens in 29 schools for better nutrition of 28,000 students in Papua New Guinea - CGIAR Research Program on Policies, Institutions, and Markets (2020)
Through a collaboration with the Government of Papua New Guinea, the Australia Department of Foreign Affairs and Trade and several other partners, data and analyses on household nutrition collected by IFPRI were used to provide insights for launching the Morobe School Gardens Project, aiming at improving nutrition of 28,000 schoolchildren in 29 schools. In November 2020, the Papua New Guinea National Education Board passed a resolution to scale up school gardens across the country.